2013
DOI: 10.1016/j.dsr2.2013.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cold-water corals in the Whittard Canyon, NE Atlantic Ocean

Abstract: a b s t r a c tThe deep-sea floor occupies about 60% of the surface of the planet and is covered mainly by fine sediments. Most studies of deep-sea benthic fauna therefore have concentrated on soft sediments with little sampling of hard substrata, such as rocky outcrops in submarine canyons. Here we assess the distribution and abundance of cold-water corals within the Whittard Canyon (NE Atlantic) using video footage from the ROV Isis. Abundances per 100 m of video transect were calculated and mapped using Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
1
26
1
Order By: Relevance
“…The fauna observed associated within the canyons studied here (see also Davies et al, this issue) have also been observed in the neighbouring Whittard Canyon , Morris, 2011and Morris et al, 2013 and other European canyon systems (Cartes et al, 2009 andGori et al, 2013). In general the observed fauna are also known from the wider area incorporating the Rockall Trough and neighbouring banks and seamounts, Porcupine Bank and Seabight (Bullimore et al, 2013, Howell et al, 2010a, Howell et al, 2010b, Narayanaswamy et al, 2013and Tyler and Zibrowius, 1992 and could not be considered to be unique to these canyon features.…”
Section: Canyon and Mini-mound Faunamentioning
confidence: 56%
See 1 more Smart Citation
“…The fauna observed associated within the canyons studied here (see also Davies et al, this issue) have also been observed in the neighbouring Whittard Canyon , Morris, 2011and Morris et al, 2013 and other European canyon systems (Cartes et al, 2009 andGori et al, 2013). In general the observed fauna are also known from the wider area incorporating the Rockall Trough and neighbouring banks and seamounts, Porcupine Bank and Seabight (Bullimore et al, 2013, Howell et al, 2010a, Howell et al, 2010b, Narayanaswamy et al, 2013and Tyler and Zibrowius, 1992 and could not be considered to be unique to these canyon features.…”
Section: Canyon and Mini-mound Faunamentioning
confidence: 56%
“…Canyons are known to support cold-water corals (CWC) , Morris et al, 2013and Orejas et al, 2009, while CWC mounds, formed by framework building scleractinian corals such as Lophelia pertusa, are common along the north-western European margin and occur in distinct regions on the Celtic Margin and Porcupine Seabight (Wheeler et al, 2007). Within the Porcupine Seabight numerous mound provinces exist, in which mounds vary in size up to giant mounds of up to 160 m high and up to 5 km in length: Hovland mounds, Magellan mounds and the Belgica mounds ( De Mol et al, 2002, Hovland et al, 1994, Huvenne et al, 2009a, Van Rooij et al, 2009and Wheeler et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there have been few studies within the Bay of Biscay. They mainly focused on scleractinian species (Joubin, 1922;Zibrowius, 1980;Reveillaud et al, 2008) and facies (Le Danois, 1948;De Mol et al, 2011;Sanchez et al, 2014) or coral habitats and assemblages, in Whittard, Dangeard or Explorer Canyons (Howell et al, 2011;Huvenne et al, 2011;Morris et al, 2013;Davies et al, 2014;Robert et al, 2015). Le Danois (1948) described both scleractinian and sand/mud facies on the continental margin of the Bay of Biscay as one of the first studies in this basin.…”
Section: Discussionmentioning
confidence: 99%
“…Ocean, and many other areas have shown that some species of cold-water corals build complex structures and produce unique demersal communities in the same way as do shallow-water coral reefs (Heifetz 2002;Heifetz et al 2005;Lundsten et al 2009;McClain et al 2010;Mol et al 2002;Morris et al 2013;Reed et al 2006;Roberts et al 2006;Stone et al 2015). Such frameworks of coldwater corals provide habitats or spawning and nursery grounds for fish and many other animals and thereby support diverse ecosystems (Baillon et al 2012;Roberts et al 2006).…”
Section: Megafaunal Composition Of Cold-water Corals and Other Deep-smentioning
confidence: 99%
“…Scleractinia are known to form large reef structures in the North Atlantic Ocean and other regions (Mol et al 2002;Morris et al 2013;Reed et al 2006). In this study, some framework-building species of the Scleractinia were and aragonite (Fabricius and Alderslade 2001).…”
Section: Many Of the Gorgonians Collected Were In The Familymentioning
confidence: 99%